Model Project Based Learning Di Pembelajaran Sains Dalam Mengembangkan Keterampilan Berpikir Tingkat Tinggi Dan Pendidikan Karakter Peserta Didik - Fatma Sukmawati (Universitas Slamet Riyadi, 2022)
The process of building character takes place continuously and should be done through education in line with the goals to be achieved. Literature studies on character building can be viewed from various aspects, including through learning a particular field of study, through developing thinking skills; integrating cognitive, affective and psychomotor domains; focusing on science and technology and imtaq, and developing a scientific attitude. Character building through the development of higher order thinking skills is an alternative in science education. Habits of mind as intelligent behavior are far more important than providing students with higher-order thinking skills through science education. Habits of mind in the sense of intelligent behavior can be trained and its achievement measured. All of this is possible if science education emphasizes project-based learning. The project-based approach in science learning is an interesting field to research, because it has a high value in improving the quality of student learning in shaping character. Keywords: Higher order thinking skills, science education, character building, project based learning.